2018
DOI: 10.1002/pros.23739
|View full text |Cite
|
Sign up to set email alerts
|

Germline genetic testing for inherited prostate cancer in practice: Implications for genetic testing, precision therapy, and cascade testing

Abstract: Background Genetic testing capability and guidelines are rapidly expanding to assess inherited prostate cancer (PCA). Clinical genetic data from multigene testing can provide insights into the germline pathogenic variant (PV) spectrum and correlates in men with PCA unselected for metastatic disease to optimize identification of men for genetic evaluation and management. Methods A retrospective cross‐sectional analysis was conducted of de‐identified clinical genetic testing data from a large commercial genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 17 publications
(70 reference statements)
0
54
0
3
Order By: Relevance
“…Another study also found that a family history of breast cancer increased the chances of identifying a germline DNA repair gene mutation in men with prostate cancer (odds ratio [OR], 1.89; 95% CI, 1.33-2.68; P5.003). 37 In a study of an unselected cohort of 3,607 patients with a personal history of prostate cancer who had germline genetic testing based on clinician referral, 11.5% had germline mutations in BRCA2, CHEK2, ATM, BRCA1, or PALB2. 38 More than 2% of Ashkenazi Jews carry germline mutations in BRCA1 or BRCA2, and these carriers have a 16% chance (95% CI, 4%-30%) of developing prostate cancer by the age of 70.…”
Section: Homologous Dna Repair Genesmentioning
confidence: 99%
“…Another study also found that a family history of breast cancer increased the chances of identifying a germline DNA repair gene mutation in men with prostate cancer (odds ratio [OR], 1.89; 95% CI, 1.33-2.68; P5.003). 37 In a study of an unselected cohort of 3,607 patients with a personal history of prostate cancer who had germline genetic testing based on clinician referral, 11.5% had germline mutations in BRCA2, CHEK2, ATM, BRCA1, or PALB2. 38 More than 2% of Ashkenazi Jews carry germline mutations in BRCA1 or BRCA2, and these carriers have a 16% chance (95% CI, 4%-30%) of developing prostate cancer by the age of 70.…”
Section: Homologous Dna Repair Genesmentioning
confidence: 99%
“…PrCa risk assessment has been primarily based on family history (FH) and screening of rare pathogenic/likely pathogenic variants (RPVs). Germline RPVs in cancer susceptibility genes have been observed in 8% to 12% of men with localized PrCa, 2 and up to 20% of men with advanced or metastatic disease 3‐6 . In addition to rare RPVs, common genetic variations also contribute to PrCa risk 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although variants that can be classified as P/LP are rare, when considered in the context of commercial multigene testing for prostate cancer susceptibility, it is clear that the number of men to whom this information could be clinically relevant is not inconsequential. For example, Giri et al report that 11% of men undergoing multigene testing for prostate cancer susceptibility (unselected for metastatic disease) had pathogenic variants in DNA repair genes that have implications for therapeutic management and cascade testing 50 …”
Section: Discussionmentioning
confidence: 99%
“…Recognised gaps in knowledge currently include cost‐effectiveness of genetic testing for PrCa susceptibility and whether the strategies for testing should include breast cancer family history information and/or Gleason score 50 …”
Section: Discussionmentioning
confidence: 99%